Review of Treatment of Reflex Sympathetic Dystrophy - Ghosh, JC; Hazra, SC; Haque, ME; Ghamsari, PS; Singha, SK (Bangladesh Journal of Medical Science, 2012)
A review study was done by searching literature through PubMed. Reflex sympathetic dystrophy is a life altering disease pathogenesis of which are not yet clearly known likewise its management protocol has not been established. Treatment of longstanding Reflex sympathetic dystrophy is empirical and of limited efficacy. This disease may lead to dreadful squeal which may need amputation for their management and few of these patients may even develop suicidal tendency. Patient with Reflex sympathetic dystrophy usually present late. It was found that the clinical presentation of RSD are too much variable, although different modalities of treatment are used either alone or in combination, the outcomes are often unpredictable and of variable efficacy. Understanding of the treatment modalities and proper selection of treatment option are essential for best outcome. Preventive measure does play a role in management of these patients. Option of treatment includes pharmacological method, sympathetic nervous system interruption, use of calcitonin and bisphosphonate. More study is required to find out the mechanism that triggers the pain and other clinical manifestation so that a standardized protocol for its management can be developed DOI: http://dx.doi.org/10.3329/bjms.v11i3.11714 Bangladesh Journal of Medical Science Vol. 11 No. 03 July12